2010
DOI: 10.1016/j.jvs.2010.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-mediated endothelial cell-selective delivery of pitavastatin induces functional collateral arteries (therapeutic arteriogenesis) in a rabbit model of chronic hind limb ischemia

Abstract: The nanotechnology platform assessed in this study (nanoparticle-mediated endothelial cell-selective delivery of pitavastatin) may be developed as a clinically feasible and promising strategy for therapeutic arteriogenesis in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 34 publications
1
40
0
1
Order By: Relevance
“…The dose of pitavastatin-NPs used in the present study was selected because of its effectiveness in previous studies from our laboratory in murine and rabbit models of hindlimb ischemia. 22,23 Further studies are needed to determine the optimal dose range and interval of pitavastatin-NPs for clinical application.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The dose of pitavastatin-NPs used in the present study was selected because of its effectiveness in previous studies from our laboratory in murine and rabbit models of hindlimb ischemia. 22,23 Further studies are needed to determine the optimal dose range and interval of pitavastatin-NPs for clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we developed a novel nanoparticle-mediated drug-delivery system (DDS) that is formulated from bioabsorbable poly(lactic-co-glycolic) acid (PLGA) polymer, and we reported that nanoparticles were taken up by a variety of cells, such as monocytes, vascular smooth muscle cells, and endothelial cells. In addition, the nanoparticle-mediated DDS showed a significant enhancement in the therapeutic effects on ischemia-induced neovascularization 22,23 and pulmonary arterial hypertension 24 in animal models compared with conventional administration. Nanoparticles are rapidly taken up by circulating monocytes and the mononuclear phagocytic system after intravenous administration, 25 and nano-sized contrast agents accumulate in atherosclerotic plaques.…”
Section: Cd11bmentioning
confidence: 98%
See 1 more Smart Citation
“…13 We therefore hypothesized that eNOS and downstream pathogenetic factors might be involved in the therapeutic effects of NP-mediated pitavastatin delivery on MCT-induced PAH. Among statins, pitavastatin was selected as the nanoparticulation compound because this drug elicited the most potent angiogenic effects in human endothelial cells 14 and the most potent inhibitory effects on human PASMC proliferation ( Figure 2) in vitro compared with other statins. We also found that NP-mediated intracellular delivery of pitavastatin showed greater inhibitory effects on PASMC proliferation and on NF-B activation in a monocyte cell line (RAW 264.7 cells) compared with pitavastatin alone (online-only Figures III and IV).…”
Section: Discussionmentioning
confidence: 99%
“…Pitavastatin was selected as the nanoparticulation compound because this drug has shown the most potent beneficial effects on human endothelial and smooth muscle cells in vitro compared with other statins. 13,14 We then used a rat model of MCTinduced PAH and examined (1) whether this NP-mediated delivery of pitavastatin into the lung is more effective than intratracheal or systemic administration of pitavastatin in attenuating the development of PAH and (2) whether this NP-mediated delivery system induces regression of established PAH.…”
mentioning
confidence: 99%